Critical Discourse Analysis Indonesian Poetry from 1966-1998 - Riefki Fajar Ganda Wiguna; Maxymilianus Soter Mite Kombong (Indonesian Journal of English Language Studies (IJELS), 2016)
The growth of Indonesian literary works began since the generation of Pujangga Baru brought literature to the surface. Many poets, novelists, and writers emerged, bringing about their works which remain popular in the present. This paper is a critical discourse analysis which aims to find the dominant ideology represented in the Contemporary Indonesian Poetry from the 1960s to the 1970s. The data were taken from Contemporary Indonesian Poetry translated by Harry Aveling (1975). There are 11 poems that were analyzed in this study. They are Sermon, Pickpocket’s Advice to His Mistress, and Prostitutes of Jakarta Unite! byW.S Rendra, Two Poems with One Title, Space, and Who Are You by Sapardi Djoko Damono, Between Us, Prayer and Image by Ajip Rosidi, and A Tale Before Sleep and Cold Unregistered by Gunawan Muhammad. By using the Seven Building Tasks proposed by James Paul Gee (2011), the researchers analyzed each poem based on the seven tasks. The result shows that the dominant ideologies in Contemporary Indonesian Poetry from the 1960s to the 1970s are in the matters of socialism and humanism. Socialism here covers the condition of social life at that time where there power abuse occurred from the powerful people towards the powerless ones. On the other hand, humanism merely covers the condition of human beings, especially Indonesians, at that time.